2016
DOI: 10.17577/ijertv5is090010
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study of Edge Detection in Noisy Images using BM3D Filter

Abstract: Edge detection in noisy images is a bargain between denoising and edge preserving capability. Hence, various smoothing filters are studied in the viewpoint of edge detection too. In this paper, a method for edge detection in noisy images has been discussed which uses BM3D (Block Matching 3D) filter for image denoising. A grayscale noisy image is denoised using Gaussian, Bilateral, Median and BM3D filters for comparison. Then the edge map of the image is obtained by applying edge detection operators like Sobel,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“… Removing the noise Noise reduction is an essential step in image processing due to its importance in obtaining better results, the block matching with three-dimensional filtering (BM3D) denoising is used in this step. Many studies shown that the BM3D filter is very important in term of noise reduction due to its results comparing with other filters [9,10]. The implementation of this filter is explained in detail in [11]  Contrast…”
Section: Telkomnika Telecommun Comput El Controlmentioning
confidence: 99%
“… Removing the noise Noise reduction is an essential step in image processing due to its importance in obtaining better results, the block matching with three-dimensional filtering (BM3D) denoising is used in this step. Many studies shown that the BM3D filter is very important in term of noise reduction due to its results comparing with other filters [9,10]. The implementation of this filter is explained in detail in [11]  Contrast…”
Section: Telkomnika Telecommun Comput El Controlmentioning
confidence: 99%